Amidoximated UHMWPE fiber using diaminomaleonitrile as a precursor possessing excellent selectivity for uranium over vanadium in natural seawater. (July 2022) - Li, Rong; Qiu, Long; Gao, Yang; Zhang, Mingxing; Xing, Zhe; Wu, Guozhong
Abstract: A novel amidoximated ultrahigh molecular weight polyethylene (UHMWPE) fiber was prepared using diaminomaleonitrile as the precursor of amidoxime group. The modified UHMWPE fibers were characterized by attenuated total reflection Fourier transform infrared spectrometry, X-ray photoelectron spectroscopy and thermogravimetric analysis, respectively. Adsorption performances were evaluated in both simulated and natural seawater. Results showed that the uranium (U) sorption capacities were 0.41 mg/g (24 h) in simulated seawater, and 0.19 mg/g (15 d) in natural seawater, respectively. Moreover, the amidoximated UHMWPE fiber presented excellent selectivity for U over vanadium (V) in both simulated (U/V mass ratio: 20.5) and natural seawater (U/V mass ratio: 3.2). Highlights: The AO based UHMWPE fiber was prepared using diaminomaleonitrile as the precursor. UHMWPE-DAMO fiber showed excellent selectivity for uranium over vanadium in seawater. The extra amino group improved selectivity for uranium via p-π conjugation effect.